Features of e-learning organization in a Modern University - Irina G. Bakanova; Jana Javorcikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
One of the most important areas of the educational system today is the widespread use of e-learning methods based on advanced information and telecommunication methods, modern pedagogical technologies The article discusses the relevance of e-learning, its possibilities in the formation of a large number of students skills necessary for their successful professional development. The necessity of using the e-learning management system in order to provide high-quality education is shown in the example of the developed e-course Foreign language for students future engineers. Besides the article shows the possibilities of LMS (Learning Management System) of the Moodle educational content management system for implementing the priority goal of the higher education system. Moreover, both positive and negative sides of using LMS are summarized in the paper. Then it gives practical suggestions for high-quality integration of e-learning in the process of teaching and learning in the educational institution of higher education Samara State Transport University on the basis of effective management of the e-learning process and good management.